Occupational Stress and Psychological Well-being – a Study on Employees in Food Delivery Services - Hidayathulla. N; M. Nirmala (Jurnal Multidisiplin Madani, 2022)
Occupational stress is the one of major problem faced by both employer and employees. Previous studies stated Occupational stress has great influence on performance and job satisfaction of employees. Employees are the back-born of any organization. So well- being of employee is an essential for success of an organization. This study is an effort to investigate the impact of occupational stress on psychological well-being of food delivery executives. The study adopted a descriptive research design and convenient sampling has been used. Data collected from 180 food delivery executives working in Malappuram district under selected food delivery companies - zomato, swiggy and Eatiko. To measure the psychological well-being of employees, study adopted modified 18 item version of ryff’s scale of psychological well-being psychological well-being. The collected data analyzed using Statistical tools like Correlation and regression